OPTIMASI RITASE SAMPAH BERBASIS MOBILE PADA DINAS LINGKUNGAN HIDUP KABUPATEN INDRAMAYU - Esti Mulyani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Ritase, or the number of effective trips made by garbage trucks, is an important indicator in determining the efficiency of waste management in a region. In Indramayu Regency, the reporting process for cleaning activities at Temporary Waste Disposal Sites (TPS) and recording fuel purchases for waste transport vehicles is still done manually. This hinders the evaluation of performance, operational accountability, and data validation in the field. This study aims to develop a mobile-based digital system to optimize waste transport ritase through real-time reporting by drivers and fuel station (SPBU) operators. Garbage truck drivers can report cleaning activities by including documentation and automatically recording TPS locations, while SPBU operators can log and upload proof of fuel purchase transactions. The system is developed using the Scrum methodology, with Flutter as the mobile application framework and Laravel as the backend API connected to a MySQL database. Test results show that the application simplifies the reporting process, speeds up data submission, and improves the accuracy of information received by the Environmental Agency. Additionally, features such as TPS location data collection and digital documentation provide added value in terms of transparency and activity validation in the field. This system is expected to improve the efficiency and effectiveness of waste transport fleet management and support fast, data-driven decision-making.